Forest fragmentation and human-wildlife conflict: assessing the impact of land use land cover change in Ranthambhore Tiger Reserve, India - Bhanwar Vishvendra Raj Singh; Amit Kumar Batar; Vivek Agarwal; Anjan Sen; Khusbhu Kulhari (Environmental Research Communications)
Habitat degradation, land-use transformation, and human-wildlife conflicts pose significant challenges to biodiversity conservation in protected areas. The Ranthambhore Tiger Reserve (RTR), a globally significant conservation landscape in India, has experienced extensive land use and land cover (LULC) changes over the past 45 years, influencing habitat connectivity and species distribution. This study aims to assess the spatiotemporal transformations in RTR’s Core and Buffer Zones from 1975 to 2020, focusing on forest loss, urban expansion, water-body depletion, and anthropo-genic land alterations. This study employs multi-temporal Landsat satellite imagery (1975, 2020), remote sensing classification techniques, Normalized Difference Vegeta-tion Index (NDVI) change detection, and Single Land Use Dynamic Degree (k%) analysis to quantify landscape changes and identify key conservation challenges. The results reveal a significant decline in dense forest (−13.81%) and shrubland (−42.83%) in the Core Zone, alongside a sharp reduction in water bodies (−63.55%), indicating increasing habitat fragmentation, environmental stress, and water scarcity. In contrast, built-up areas expanded exponentially (+7183.18%), highlighting rapid built-up en-croachment. The Buffer Zone exhibited a 42.07% increase in dense forest, reflecting conservation efforts and natural regeneration, yet also faced substantial built-up ex-pansion (+325.35%) and water body depletion (−56.92%), exacerbating human-wildlife interactions. NDVI analysis further indicated localized improvements in vegetation health but persistent degradation hotspots. The findings emphasize the need for integrated conservation strategies that address habitat fragmentation, water resource depletion, and human-wildlife conflicts. Restoring ecological corridors, implementing sustainable water management, strengthening community led conservation initiatives, and enforcing land-use regulations are key recommendations for mitigating further degradation. This study provides a critical baseline for long-term conservation plan-ning, guiding policy interventions to ensure the ecological integrity and coexistence of humans and wildlife in RTR.